1992
DOI: 10.1016/0014-5793(92)80991-o
|View full text |Cite
|
Sign up to set email alerts
|

Cellobiose oxidase from Phanerochaete chrysosporium Stopped‐flow spectrophotometric analysis of pH‐dependent reduction

Abstract: Cellobiose oxidase (CBO) from Phaneroehaete cho,sospor [um can utili~ dichlorph¢nol-indoplmnol (CMnd) and cytochrorne c as effective electron aeceptors for the oxidation of c¢llobiose. However, the pH dependencies of activity for these electron aew.eptors me significantly different. Both compounds act as effective electron acceptors at pH 4..2, whereas only dichlorophenol-indophenol is active at pH ri.9. To explain this discrcpanc),, the pH dependencies of the reduction rates of FAD and home, respectively, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
1
26
1
Order By: Relevance
“…The reduction of triiodide was also reported [69]. The reduction of these electron acceptors usually takes place at the flavin [70], but as basidiomycete CDHs can shuttle electrons efficiently to the haem at pH values below 5.5 [59] and ascomycete CDHs can shuttle electrons efficiently to the haem even at neutral or increased pH values [37,40,66], it is obvious that oneelectron acceptors can also be reduced at the haem. It is common belief that two-electron acceptors are reduced directly at the flavin domain, but opinions differ pertaining to the reduction of one-electron acceptors.…”
Section: Catalytic Mechanism Of the Oxidative Half-reactionmentioning
confidence: 94%
See 1 more Smart Citation
“…The reduction of triiodide was also reported [69]. The reduction of these electron acceptors usually takes place at the flavin [70], but as basidiomycete CDHs can shuttle electrons efficiently to the haem at pH values below 5.5 [59] and ascomycete CDHs can shuttle electrons efficiently to the haem even at neutral or increased pH values [37,40,66], it is obvious that oneelectron acceptors can also be reduced at the haem. It is common belief that two-electron acceptors are reduced directly at the flavin domain, but opinions differ pertaining to the reduction of one-electron acceptors.…”
Section: Catalytic Mechanism Of the Oxidative Half-reactionmentioning
confidence: 94%
“…In order to shed light on the mechanism of electron transfer in CDH, the reduction of P. chrysosporium CDH by cellobiose has been investigated by rapid-kinetics studies using stopped-flow spectrophotometry [56,[58][59][60][61][62][63]. The rate of flavin reduction depends on the cellobiose concentration but reaches a rate limit of approx.…”
Section: Interdomain Electron Transfermentioning
confidence: 99%
“…It has been reported that both cytochrome c and DCPIP were reduced by CDH at pH 4.2, whereas only DCPIP was reduced effectively at pH 5.9. This phenomenon was explained by stopped-flow kinetic study that both flavin and heme were reduced at a high rate at pH 4.2, whereas only flavin reduction proceeded quickly at pH 5.9 (18). From these observations, the reduction of cytochrome c is dependent on heme, and an electron is transferred from cellobiose to this electron acceptor via both FAD and heme, whereas the reduction of DCPIP is catalyzed only by flavin.…”
mentioning
confidence: 95%
“…Jones and Wilson (27) observed that the rate constant for heme iron reduction in CDH increases with enzyme concentration and interpreted this as due to the intermolecular reduction of the heme center by flavin groups; whereas, in the case of flavocytochrome b 2 , electron transfer from flavin to heme is intramolecular (79). Samejima et al (28) studied the effect of pH on the reduction of cytochrome c and dichlorophenol-indophenol by CDH.…”
Section: Kinetic Studiesmentioning
confidence: 99%